2001
DOI: 10.1001/archotol.127.10.1216
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Electrical Stimulation of the Hypoglossal Nerve in Obstructive Sleep Apnea

Abstract: The findings demonstrate the feasibility and therapeutic potential for hypoglossal nerve stimulation in obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
189
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 265 publications
(207 citation statements)
references
References 36 publications
6
189
0
12
Order By: Relevance
“…The severity of upper airway obstruction during sleep is related to quantitative differences in pharyngeal collapsibility, as reflected by elevations in the critical closing pressure (Pcrit). Moreover, as Pcrit fell below a minimally negative threshold of approximately 25 cm H 2 O, sleep apnea remitted, suggesting that changes in Pcrit play a pivotal role in the pathogenesis of this disorder (see Figure 1, right) (25,(57)(58)(59)(60)(61). In further studies, investigators have demonstrated that Pcrit is determined by mechanical and neural factors that regulate pharyngeal collapsibility (62)(63)(64)(65)(66)(67).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 95%
“…The severity of upper airway obstruction during sleep is related to quantitative differences in pharyngeal collapsibility, as reflected by elevations in the critical closing pressure (Pcrit). Moreover, as Pcrit fell below a minimally negative threshold of approximately 25 cm H 2 O, sleep apnea remitted, suggesting that changes in Pcrit play a pivotal role in the pathogenesis of this disorder (see Figure 1, right) (25,(57)(58)(59)(60)(61). In further studies, investigators have demonstrated that Pcrit is determined by mechanical and neural factors that regulate pharyngeal collapsibility (62)(63)(64)(65)(66)(67).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 95%
“…Subsequently, investigators documented arousal thresholds during submental stimulation, which confounded assessment of airflow responses and limited clinical applicability of this technique during sleep (31,32). Investigators further refined the stimulation technique by inserting temporary fine-wire electrodes into lingual muscles, and demonstrated that protrusor muscle stimulation mitigated and retractor muscle stimulation worsened pharyngeal patency during sleep (13,16,18,19,33). In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19).…”
Section: Arousalsmentioning
confidence: 99%
“…Investigators further refined the stimulation technique by inserting temporary fine-wire electrodes into lingual muscles, and demonstrated that protrusor muscle stimulation mitigated and retractor muscle stimulation worsened pharyngeal patency during sleep (13,16,18,19,33). In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19). Additional studies with implantable nerve cuff (13) and fine-wire electrodes have demonstrated responses to selective lingual muscle stimulation during sleep and anesthesia (13)(14)(15)(16)(17).…”
Section: Arousalsmentioning
confidence: 99%
See 2 more Smart Citations